Profitability and Leverage: Different Effects of Negative Profits? - Bensaadi, Iswadi; Adnan, Adnan; Albra, Wahyuddin (Universitas Syiah Kuala, 2023)
Objective This study aims to examine the effect of profitability on leverage in firms with negative profits and the sensitivity of the COVID-19 pandemic in explaining the effect of profitability on leverage.Design/Methodology This study uses unbalanced panel data for 660 firm-year observations over 4 (four) years from 2018 to 2021 on non-financial service firms. Two-stage least square regression was utilized to examine the effect of profitability on leverage.Results Consistent with several previous studies, this study indicates that profitability negatively affects leverage and has similar results in firms with negative profits. Another finding is that the COVID-19 pandemic is not sensitive to explaining the effect of profitability on leverage. Both the pre-COVID-19 pandemic and during the COVID-19 pandemic, profitability has a similar effect on leverage.Research limitations/implications This study is conducted over a short period, only four years. The study provides a new perspective on the effect of profitability on leverage in companies with negative profits and the pecking order theory in explaining the relationship between profitability and leverage in the Indonesian context.Novelty/Originality This study examines the effect of profitability on leverage in firms with negative and positive profits using a two-stage least square (2SLS) in the Indonesian context.